Inovações tecnológicas na sexagem, manejo reprodutivo e crescimento do pirarucu, Arapaima gigas (SCHINZ, 1822), (Actinopterygii, Arapaimidae) cultivado no Centro de Pesquisas em Aquicultura Rodolpho von Ihering (CPA) do DNOCS, Pentecoste, Estado do Ceará - Carreiro, Carlos Riedel Porto (2012)
The present study deals with aspects of sexing, breeding, nursery and growth of pirarucu, Arapaima gigas, presented in four chapters. The first chapter revealed historical aspects of introduction and reintroduction of pirarucu. Now, the reintroduction of pirarucu in the past decade had another purpose, which was the development of studies in research management, growth and reproduction. In the second chapter we have developed different technologies for pirarucu sex identification: ultrasound, which generated different images for male and female gonads; laparoscopy that generated clear images of the gonads, and can distinguish gonadal stages. Was a tested variation in levels of estradiol and testosterone hormones in fingerling and juvenile, not being able to use this methodology to determine the sex because there is no correlation between the concentration of hormones and the length of pirarucus. RAPD reactions were used to determine polymorphisms with sex of Arapaima gigas, indicating the need for further studys. In third chapter we studied some of the many aspects that helped the reproduction management: The rainfall showed a positive correlation with the frequency of spawn pirarucu in Ceara state, Brazil; This chapter also describes the utilization of electronic transponders; No mortality was recorded during two years study, the introduction of electronic transponders also revealed a new dynamic of courtship behavior, with resultant formation of new pirarucu couples. Another aspect described in the third chapter was the pirarucu food training, step of importance in pirarucu fish farming. There were two systems of training food – The first one use gradual transition from live food to commercial food and seconds left fingerling in parental care. The system of weaning showed lower survival rates, however, righter growth and weight. The gradual transition showed higher survival and lower growth and weight. Anesthetics were tested (chloroform and menthol); Menthol has been used successfully in adults and juveniles with administration by spray gills. The chloroform was effective anesthetics immediately after inhalation, running directly to the stage of surgical anesthesia. The fourth chapter studies were performed growth and weight of pirarucu fry and juveniles to commercial size, initially using samples with an average weight of 1g, ending after 19 months of cultivation, with an average weight of 10,000 g.